2012
DOI: 10.1007/s10926-012-9376-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Self-Reported Work Ability and Usefulness of Interventions Among Sick-Listed Patients

Abstract: Methods A prospective cohort study was performed including 810 newly sick-listed patients (MSD 62% and MD 38%). The baseline questionnaire included sociodemographic characteristics and measures of work ability. The 3-month follow-up questionnaire included measures of work ability, type of intervention received, and judgment of usefulness.Results Twenty-five percent received medical intervention modalities (MI) only, 45% received a combination of medical and rehabilitative intervention modalities (CRI) and 31% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
1
15
0
1
Order By: Relevance
“…The finding that early rehabilitation interventions were only prescribed in approximately onefourth of sickness certificates is in agreement with a concurrent study conducted in the same county council, which included patients with MSD and MD who were certified sick leave by PHC or OHS [11]. Wåhlin et al observed that within three months, 45% of these patients reportedly have received a combination of medical and rehabilitative intervention modalities, and 31% had also received work-related interventions [11].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The finding that early rehabilitation interventions were only prescribed in approximately onefourth of sickness certificates is in agreement with a concurrent study conducted in the same county council, which included patients with MSD and MD who were certified sick leave by PHC or OHS [11]. Wåhlin et al observed that within three months, 45% of these patients reportedly have received a combination of medical and rehabilitative intervention modalities, and 31% had also received work-related interventions [11].…”
Section: Discussionsupporting
confidence: 76%
“…Wåhlin et al observed that within three months, 45% of these patients reportedly have received a combination of medical and rehabilitative intervention modalities, and 31% had also received work-related interventions [11]. When only MD and MSD were included in the current analysis, early rehabilitation was prescribed in 45% of the certificates issued for these two diagnostic groups.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Other caregivers were consulted in a few cases. Rehabilitative activities were healthcare advice, behavioural treatment (therapeutic conversation, cognitive therapy, body awareness), exercise therapy/physical activity, manual treatment (manual, acupuncture/TENS), ergonomic/ADL, equipment/orthosis and other [17]. The interventions included healthcare consultations with personal meetings as well as indirect contacts, i.e.…”
Section: Rehabilitative Measures In the Public Healthcare Systemmentioning
confidence: 99%